Identification of surface water and groundwater relationship at Universiti Tun Hussein Onn Malaysia (UTHM) Campus - Riwayat, Akhtar Izzaty (2018)
Descriptions of the surface water and groundwater relationships are required for enhanced water resource management. The increase in population and rapid development has boosted the demand and use of water supply each year in Parit Raja. Moreover, no further research related to relationships between both sources has been carried out in this flat topography area. Thus, the descriptions of surface water and groundwater relationships are required to enhance water resource management in UTHM campus in order to meet the future demands. The Schlumberger array was used for Electrical Resistivity Imaging (ERI) during data acquisition to identify potential shallow aquifers and suitable locations for boreholes which function as observation wells. Three new boreholes were installed and the ERI results showed that this area recorded low resistivity values less than 10 Ωm with potential groundwater at varying depths between 10 to 30 m. Meanwhile, in hydrochemical analysis the chemical properties of major cations (Na+, Mg2+, K+, Ca2+) and anions (Cl-, SO42-, NO3-) were analysed to characterise surface water and groundwater. The result showed that all surface water is characterized by Ca2+ - Mg2+- Cl- - SO42- types of fresh water, while the groundwater is characterized by Na-Cl type of saline water due to seawater intrusion which indicated that the interaction of surface water and groundwater were not occur in this study area and the recharge areas might be located outside this area. This result interpreted that the lakes and swale were remained in good quality whereas groundwater at this aquifer was seriously intruded by seawater. Even though, the isotopic composition for δ18O and δ2H values of surface water were relatively similar to that of groundwater samples in Station A and Station C as they varying between -4.32%o to -9.74%o for δ18O and from -33.86%o to -65.82%o for δ2H, these surface water samples had low salinity (Cl- < 20 mg/l) compared with that of groundwater (Cl- > 3000 mg/l). This result could be explained by effects of evaporation and seawater intrusion on these groundwater samples rather than interaction with surface water. Thus, the relationships of surface water and groundwater might not occur in UTHM campus and the recharge areas might be located outside this area.